Effect of fly ash on tensile properties of ultra-high performance fiber reinforced cementitious composites (UHP-FRCC). Issue 6 (2nd November 2018) - Shaikh, Faiz UddinAhmed; Nishiwaki, Tomoya; Kwon, Sukmin
Abstract : This article presents and compare the tensile strain hardening behavior, compressive strength, energy absorption, and CO2 emission of environmental friendly ultrahigh performance fiber reinforced cementitious composites (UHP-FRCC) containing various fly ash contents as partial replacement of premix cement (consisted of 82% low heat cement and 18% silica fume). Six series of UHP-FRCC are considered in this study. The first two series are control series while the rest four series contain 20, 30, 40, and 50% fly ash as partial replacement of premix cement. A small amount of nano silica (2 wt.%) is also added to compensate the low early age strength properties of the fly ash based UHP-FRCC. Results show that fly ash contents of 30–40% exhibited better compressive strength, tensile strain hardening behavior, and energy absorption than the other fly ash contents in the UHP-FRCC. The UHP-FRCC containing 40% fly ash shows about 12, 14, 10, and 22% reduction in compressive strength, ultimate tensile strength, ultimate tensile strain, and energy absorption capacities, respectively, than the control, while its CO2 emission is about 35% lower than the control. The reported properties of UHP-FRCC containing 40% fly ash are still higher than other reported UHP-FRCC containing other SCMs as well as many reported UHP-FRCC containing no SCMs except the silica fume.